The Usage Of Language In Multi-Perspective - Azhar, Imam (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2017)
Language is obviously a vital tool. Not only is it a means of communicating thoughts and ideas, but it forges friendships, cultural ties, and economic relationships.Throughout history, many have reflected on the importance of language. For instance, the scholar Benjamin Whorf has noted that language shapes thoughts and emotions, determining one’s perception of reality. John Stuart Mill said that Language is the light of the mind. Language is not only a vehicle for the expression of thoughts, perceptions, sentiments, and values characteristic of a community; it also represents a fundamental expression of social identity. In this work, Language is seen from philosophical, psychological, and psicolinguistical sights. In addition, it alsosees the differences of language used among human kinds, they are; the use of language in the area of common people, the use of language in scientific knowledge.The last but not least, it also discusses the function and the benefit of language in critical thinking.